Metrological Characterization of a CO2 Laser-Based System for Inscribing Long-Period Gratings in Optical Fibers - Valencia-Garzón, Sebastian; Reyes-Vera, Erick; Galvis-Arroyave, Jorge; Montoya, Jose P.; Gomez-Cardona, Nelson; Galvis Arroyave, Jorge Luis (MDPI AG, 2022)
A CO2 laser-based system was studied and implemented to produce asymmetric long period fiber gratings (LPFG) with a large attenuation peak, high reproducibility, and high stability. The first half of this study provides a mathematical uncertainty model of the CO2 laser-based approach that takes into account various mechanical and thermal effects that impact this production technique. This is the first time that metrological analysis and modeling are performed on the CO2 laser-based engraving technique. Following that, the engraved system’s quality was assessed using a microscopic approach to confirm mechanical characteristics such as grating period, engraved spot width, and penetration depth, demonstrating that, if the thermal and mechanical components of the overall system are correctly managed, it is feasible to have very low inaccuracy. Lastly, the LPFG performance as temperature and strain sensors was tested, and the findings show that they had good linearity in both circumstances. Thus, the temperature sensor had a maximal sensitivity of 58 pm/°C when measuring temperature changed from 20 to 97 °C, but the strain sensor had sensitivity of 43 pm/με when measuring strain variations from 5.59 to 25 με. As a result, the model and results presented in this paper can be utilized to create a platform for the metrological management of lengths involved in the process of manufacturing LPFGs, devices that are widely employed in the creation of sensors and communications devices.